Interaction of ions and water in gramicidin A channels: streaming potentials across lipid bilayer membranes (The Rockefeller University Press, 1978)
For very narrow channels in which ions and water cannot overtake one another (single-file transport), electrokinetic measurements provide information about the number of water molecules within a channel. Gramicidin A is believed to form such narrow channels in lipid bilayer membranes. In 0.01 and 0.1 M solutions of CsCl, KCL, and NaCl, streaming potentials of 3.0 mV per osmolal osmotic pressure difference (created by urea, glycerol, or glucose) appear across gramicidin A- treated membranes. This implies that there are six to seven water molecules within a gramicidin channel. Electroosmotic experiments, in which the water flux assoicated with current flow across gramicidin- treated membranes is measured, corroborate this result. In 1 M salt solutions, streaming potentials are 2.35 mV per osmolal osmotic pressure difference instead of 3.0 mV. The smaller value may indicate multiple ion occupancy of the gramicidin channel at high salt concentrations. Apparent deviations from ideal cationic selectivity observed while attempting to measure single-salt dilution potentials across gramicidin-treated membranes result from streaming potential effects.